Strain hardening under non-proportional loading in polycrystalline aluminum alloys - OSIPIUK, W.; ŁUKASZEWICZ, K. (Engineering Transactions, 2008)
In the paper it is postulated that the so-called common slip domains influence the character of the strain hardening phenomena for complex loading paths. The slip domains were evaluated on the basis of the Batdorf–Budiansky slip theory of plasticity. Evolution of a yield surface for different non-proportional tension-torsion loading paths was determined for PA4 aluminum alloy and the hypothesis that the strain hardening depends on the development of the common slip domains was shown to be justified.